A follow-up and treatment model for pediatric eating disorders: examination of the clinical variables of a child and adolescent psychiatry eating disorder outpatient clinic - Özbaran, N. Burcu; Erbasan, Zeynep İrem; Yılancıoğlu, Hazal Yağmur; Çek, Didem; Taş, Begüm Yuluğ; Tokmak, Sibel Helin; Bildik, Tezan (Frontiers in Psychiatry, 2023)
Anorexia nervosa and other eating disorders are common in children and adolescents and are characterized by symptoms such as food restriction, efforts to lose weight, fear of gaining weight and impaired body image. Anorexia nervosa is a life-threatening psychiatric disorder and its management in the outpatient setting can be challenging for clinicians. The aim of this study was to introduce the subunit service model developed for the multidisciplinary diagnosis and management of eating disorders in the outpatient setting and to evaluate the clinical follow-up of patients. The medical records of 37 patients who were followed up by the eating disorders team at our clinic between 2018 and 2022 were reviewed. The study was designed as retrospective case study. A diagnosis was made according to DSM-5 and a treatment plan was developed for each case. Body mass index (BMI), Clinic Global Impression (CGI) scale scores, duration of follow-up, number of interviews and other scale scores (The Turgay Attention Deficit Hyperactivity Disorder Scale and the Autism Spectrum Screening Questionnaire Scale) of 37 patients aged 12-17 years diagnosed with an eating disorder and followed up in our clinic were statistically compared. The Eating Disorder Follow-up Model developed and applied in our clinic had a positive effect on patients BMI scores, a significant improvement in CGI scores was observed. We believe that this multidisciplinary system will serve as a model for other mental health centers by raising awareness and guiding mental health professionals in the follow-up and treatment of eating disorders.